Radikalisme dalam Bahan Ajar dan Analisa Wacana Kritis Perspektif Van Dijk Terhadap Materi PAI Tingkat SMA - Winarto Eka Wahyudi (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2017)
: This article explore aboute radicalism, discourse of radicalism described on PAI textbooks in senior high school (SMA) became a quaint discourse amid the diversity of the Indonesian nation. Thus, sticking existence in 2014 and then, a national issue because indicated propagate the teachings legitimize the killing of another person under the pretext purify monotheism. With this method of writing kualititif non-interactive, because using this type of literature research study, the research discovered important findings. Namely, there are three discourses that is used as a campaign idea gospel radicalism, among others; validity to fight and lay the others, crimes verbal and literal as well as encouragement to keep people on the prophetic role of the clergy. In addition, to strengthen the idea of radicalism, wacanapun built with some of the linguistic elements, among others; thematic (text structure that leads to the violent ideology), schematic (preparation discourse radicalism narrated as a whole in one specific topic), semantics (loading prejudice to sentence / the subject matter that has implications for the meaning of understanding radical), syntax (structure indicates logic constituent used in narrating teaching materials, namely using deductive reasoning causality) while rhetorically authors assert his ideas through reasoning resistance, vis a vis, black-white, bad cop and good cop.Keywords; Radicalism, textbooks, discourse